The Pressing Plates, the Screws, and the Nuts: Aramaic as a Contact Language in the Oil-Pressing Industry of the Holy Land - Neishtadt, Mila (Aramaic studies, 2025)
This article examines Aramaic as a contact language in oil-pressing terminology in the Holy Land as documented for nearly two millennia. It focuses on three obscure Rabbinic Hebrew (RH) terms from the Baraita concerning the oil and wine press: ‮dfyn‬‎ dpyn "plates," ‮lṿlvyn‬‎ lwlbyn lit. "palm fronds," and ‮ʿdshyn‬‎ ʿdšyn lit. "lentils." These are clarified through comparison with Christian Palestinian Aramaic (CPA) oil-press terms lwlybʾ "screw" and ṭwlwpḥtʾ lit. "lentil," meaning "nut board," and with Palestinian Arabic (PA) lōlab "screw" and ṭlēfḥa "nut board." The PA terms provide crucial evidence for interpreting the CPA lexemes, which, in turn, shed light on the original RH usage. From the perspective of material culture, the CPA terms likely relate to parts of a lever-and-screw press, with the screw and nut board forming a cross. The Baraita likely refers to any type of screw press, in which all three components—‮dfyn‬‎ dpyn "pressing plates," ‮lṿlvyn‬‎ lwlbyn "screws," and ‮ʿdshyn‬‎ ʿdšyn "nuts, nut boards"—were wooden, and thus shared halachic purity regulations. A diachronic analysis shows lwlb was borrowed from Akkadian into Aramaic, then into Hebrew and Arabic, though in the latter, only with the meaning "screw, coil." The PA ṭlēfḥa "nut, nut board" likely reflects an inherited Aramaic substrate word. This study contributes to Semitic lexicography, early Christianity, Talmudic scholarship, and the history of material culture in the Holy Land.